The development of the psychologist's professional knowledge : A study of graduated in the U.N.L.P., their insert in the educational field - Compagnucci, Elsa Rosa; Cardós, Paula Daniela (2009)
Los estudios sobre la formación de profesores en psicología nos fueron situando en el proceso de construcción del conocimiento profesional tanto en profesores como en psicólogos que ejercen la docencia, visualizando el papel que en él asumen los conocimientos construidos en los ámbitos académico y profesional y la relación entre ambos.
The studies on the formation of psychology's professors were locating us in the construction process of the professional knowledge in professors but in psychologists that exercise the teaching too, visualizing the paper that built knowledge assumed between both environments (academic and professional) and the relationship between them.
Keywords: Conocimiento profesional; Psicólogo; Campo educativo; Professional knowledge; Psychologist; Educational field; Enseñanza de la psicología; Psicólogos